Role of admission cardiotocography and amniotic fluid index on perinatal outcome in low risk pregnancy at term - Patnaik, Manasi; M, Tejaswini; Rath, Sudhanshu Kumar; Naaz, Shaik Afrah (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Fetal surveillance even in normal or low risk pregnancy is essential to ensure safe parturition with minimum intervention. Cardiotocography (CTG) and clinical estimation of amniotic fluid volume (AFV) measured as amniotic fluid index (AFI) are two tests that are easily available in the labor room and can be used to identify fetal well-being. Our study aimed to evaluate role of admission cardiotocography (CTG) and amniotic fluid index (AFI) on perinatal outcome in low risk pregnancy at term. Methods: The study was conducted as a prospective observational study. All low risk pregnant women at term admitted to the labor ward in early or established labour between September 2018 and August 2020 were included in the study. They underwent admission CTG and AFI assessment using ultrasonography. All parameters including CTG changes, mode of delivery, AFI, presence of meconium, APGAR score at 1 and 5 mins, need for admission in neonatal ICU and perinatal mortality were recorded. Quantitative data was compared using chi square test. Results: A total of 180 patients were included in the study. Majority of the women belonged to the age group of 30-35 years. Abnormal CTG showing fetal distress was seen in 105 (58.33%) cases. Non-reactive CTG was significantly associated with meconium stained liqour, requirement for LSCS, still birth, fetal distress, APGAR <7 at 1 and 5min and NICU admission (p<0.001). The association of low AFI with non-reactive CTG had statistically significant impact on perinatal outcomes like low birth weight, requirement for LSCS, fetal distress, APGAR <7 at 1 and 5 mins and NICU admissions. Conclusions: Admission CTG is a simple non-invasive test that can serve as a screening tool in low risk obstetric population to detect fetal distress already present or likely to develop and prevent unnecessary delay in intervention. Thus, it may help in preventing fetal morbidity and mortality.